Development of Android-Based Learning Media in The Subjects of Planning and Installation Video Audio System - Joni Andrian; Hasan Maksum (STAI Miftahul Ula Nganjuk, 2020)
This research aims to produce products in the form of android-based learning media that are valid, practical and effective in the subjects of Planning and Installation of Audio Video Systems. Development of android-based learning media using R&D research method with 4D development procedure (define, design, development and disseminate). The subjects in this study were students of class XII Audio Video Engineering SMK Negeri 1 Batipuh. The results showed the feasibility of android-based learning media with media expert test results obtained an average of 89% with the category